(untitled) (CIPEEX, 2022)
THIS MODULE THAT WAS DEVELOPED AIMS TO ELABORATE AND SEND NOTIFICATIONS TO USERS OF THE UNICASH MOBILE APPLICATION, IT WILL BENEFIT STUDENTS FOR THEIR PERFORMANCE IN ACTIVITIES. THE APPLICATION WILL BE AIMED AT STUDENTS OF THE EVANGELICAL UNIVERSITY OF GOIS, WHERE THE STUDENT CAN COLLECT POINTS WHEN DOING THE ACTIVITIES AND LATER EXCHANGE THESE POINTS FOR PRIZES. THE NOTIFICATION MODULE WORKS IN CONJUNCTION WITH OTHER AREAS, IN ORDER TO COLLECT DATA FROM OTHER SECTORS RESULTING IN THE SENDING OF PUSH NOTIFICATIONS VIA EMAIL AND SMS. THE NOTIFICATIONS SENT INCLUDE REGISTRATION INFORMATION, FINANCIAL TRANSACTIONS THROUGH THE APPLICATION, EXPIRATION OF COUPONS, PROMOTIONS IN THE STORE, REDEMPTION OF POINTS, AMONG OTHERS. WITHIN THE APPLICATION, WILL BE INTEGRATED THE STORES PRESENT IN THE EDUCATIONAL INSTITUTION, PROVIDING THE STUDENT WITH THE EXCHANGE OF POINTS FOR ITEMS IN THE ONLINE STORE. DURING THE DEVELOPMENT OF THE MODULE WAS CARRIED OUT THE CREATION OF A DATABASE AND THE ENDPOINTS OF THE NOTIFICATIONS FOR EACH EVENT, WAS ALSO MADE THE DEVELOPMENT OF THE NOTIFICATION SCREEN AND THE DOCUMENTATION OF THE API. &NBSP; &NBSP;